Forced circumcision of men (abridged). Issue 8 (6th September 2013) - Glass, Michael
Abstract : The forced circumcision of men is a widespread human rights abuse that often accompanies other human rights violations. It occurs in clashes between circumcising and non-circumcising cultures, or when individuals in circumcising cultures reject circumcision. This article documents the forced circumcision of men against their will, shows how evidence of forced circumcision has been downplayed and discounted, and outlines and discusses some measures that could help to reduce its prevalence.